2020
DOI: 10.9734/jammr/2020/v32i2330720
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Comorbidities among Children with Attention Deficit Hyperactivity Disorders

Abstract: Background and Purpose: Attention Deficit Hyperactivity Disorder (ADHD) is the most common neurodevelopmental disorder in children. The purpose of this study is to explore the rate of psychiatric comorbidities among children with ADHD and investigating the impact of comorbidities on function of children. Subjects and Methods: Sixty-four children of both genders who fulfilled DSM-5 criteria for ADHD were included. All subjects were subjected to IQ assessment, Kiddie Schedule for Affective Disorders and Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
1
0
0
Order By: Relevance
“…Intellectual disability was the most common comorbidity among patients with primary diagnosis of ADHD, autistic spectrum disorder, affective disorders, psychotic disorders and epilepsy in the current study, while around one-fourth of the intellectual disability patients had comorbid epilepsy. This is in keeping with the results of the study by Shaaban et al [31] reporting the oppositional defiant disorder (ODD) as the most common comorbidity among ADHD patients if intellectual disability is excluded. Study by Zhang and Ji [32] reported that all the patients suffering from autistic spectrum disorder had intellectual disability, supports the findings of our study where sixty out of sixty-one patients with ASD had intellectual disability.…”
Section: Discussionsupporting
confidence: 90%
“…Intellectual disability was the most common comorbidity among patients with primary diagnosis of ADHD, autistic spectrum disorder, affective disorders, psychotic disorders and epilepsy in the current study, while around one-fourth of the intellectual disability patients had comorbid epilepsy. This is in keeping with the results of the study by Shaaban et al [31] reporting the oppositional defiant disorder (ODD) as the most common comorbidity among ADHD patients if intellectual disability is excluded. Study by Zhang and Ji [32] reported that all the patients suffering from autistic spectrum disorder had intellectual disability, supports the findings of our study where sixty out of sixty-one patients with ASD had intellectual disability.…”
Section: Discussionsupporting
confidence: 90%